Experimental autoimmune encephalomyelitis as a model of Multiple Sclerosis : pathogenesis of atypical disease and tolerance induction in chronic progressive disease - Curtis II, Alan Dale (East Carolina University, 2015)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS) of putative autoimmune origin characterized by focal inflammatory lesions together with demyelinating plaques in the periventricular and perivascular regions of the CNS white matter. In this study, a novel model of experimental autoimmune encephalomyelitis (EAE) was developed in the Lewis rat to bridge the gap between stereotypical EAE and the heterogeneous clinical presentation of MS. The disease was associated with a rostral distribution of neutrophilic infiltration and severe, non-typical clinical symptoms. Clinical presentation was marked by rigid paralysis, vertigo, body contortion, forelimb involvement without hindlimb paralysis, etc. In comparison, 'classic' EAE was defined by caudal lesion distribution and a predictable ascending flaccid paralysis. This model represents a key advance in the field and will facilitate the study of potential therapeutics in a disease that more closely resembles human MS. Historically, MS patients have been prescribed interferon beta (IFN-[beta]), broad spectrum immunosuppressive agents, and monoclonal antibody (mAb) therapy resulting in sub-optimal clinical outcomes. Therapeutic approaches that induce antigen-specific immune tolerance are a key goal in the management of autoimmune disease. These antigen-specific therapies would preserve the integrity of the T cell repertoire by specifically targeting auto-reactive T cell clones. Our laboratory has developed a novel tolerogenic vaccine platform based on cytokine-neuroantigen (NAg) fusion proteins to promote T cell tolerance in mice and rats. We have also described the mechanisms behind the tolerogenic activity of a protein consisting of the granulocyte-macrophage colony stimulating factor (GM-CSF) fused to an encephalitogenic peptide (amino acids 35-55) of the myelin oligodendrocyte glycoprotein (MOG) (GMCSF-MOG). These studies revealed two separate mechanisms of action. The first mechanism relied on elaboration of interferon gamma (IFN-[gamma]) and nitric oxide (NO), because GMCSF-MOG resulted in partial protection from EAE in mice deficient in the IFN-[gamma] receptor or the inducible nitric oxide synthase (iNOS). Tolerance induction was reliant on targeting of the MOG35-55 peptide to pro-inflammatory subsets of antigen presenting cells (APC) that resulted in decreased antigen-specific T cell proliferation. The second mechanism involved the differentiation of FoxP3+ induced regulatory T cells (TREG). GMCSF-MOG administered to mice expressing a MOG35-55-specific transgenic T cell receptor (TCR) showed at least a 4-fold increase in the percentages of FoxP3+ MOG35-55-specific T cells relative to unconjugated MOG peptide or saline treatments. Further, administration of a mAb specific for the [alpha] chain of the IL-2 receptor (cluster of differentiation 25, CD25) reversed tolerance induced by GMCSF-MOG treatment. These observations indicated that the dominant inhibitory action of GMCSF-MOG was due to activation and proliferation of TREG. Taken together, the work presented here showed that GMCSF-MOG was a potent, tolerogenic vaccine capable of priming T cell tolerance in vivo even within heavily adjuvant-primed pro-inflammatory environments. Thus, we concluded that MOG35-55-specific T cell modulation and MOG35-55-specific TREG dominance acted synergistically to facilitate active tolerance. These types of approaches represent an important potential strategy for tolerance induction in MS patients.
Keywords: Immunology; Autoimmunity; Experimental autoimmune encephalomyelitis; Multiple sclerosis; Tolerance; Vaccines; Encephalomyelitis, Autoimmune, Experimental--metabolism; Multiple Sclerosis--metabolism; Adaptive Immunity